1997
DOI: 10.1080/01621459.1997.10473636
|View full text |Cite
|
Sign up to set email alerts
|

On the Determination and Construction of Optimal Block Designs in the Presence of Linear Trends

Abstract: This article considers experimental situations in which v treatments are to be applied to experimental units arranged in b blocks of size k and where there may be unknown or uncontrollable linear trends (possibly different) within blocks. Methods are given for determining and constructing universally optimal designs for such situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…As k À 1 is the highest possible degree to which a block design with block size k can be orthogonal, a design that is orthogonal to a (k À 1Þth order time trend will simply be referred to as a trend-free design. Jacroux et al (1995Jacroux et al ( , 1997 and Jacroux (1998) tackle the problem of identifying and constructing block designs for comparing several treatments in the presence of possibly different linear trends within the blocks. However, it is known that for certain combinations of the design parameters trend-free block designs do not exist.…”
Section: Time Trend Effectsmentioning
confidence: 99%
“…As k À 1 is the highest possible degree to which a block design with block size k can be orthogonal, a design that is orthogonal to a (k À 1Þth order time trend will simply be referred to as a trend-free design. Jacroux et al (1995Jacroux et al ( , 1997 and Jacroux (1998) tackle the problem of identifying and constructing block designs for comparing several treatments in the presence of possibly different linear trends within the blocks. However, it is known that for certain combinations of the design parameters trend-free block designs do not exist.…”
Section: Time Trend Effectsmentioning
confidence: 99%
“…The research focus is usually on combinatorial construction of exact designs orthogonal to time trend (or trend free). These are designs that satisfy that no information is lost due to the time trend (see, e.g., Jacroux et al [1997], Bailey et al [1992]).…”
Section: Trend Resistant Designsmentioning
confidence: 99%
“…For example, any experiment that consists of multiple trials performed in a time sequence may be subject to a nuisance time trend caused by the ageing of the material used for the experiment, wearing down of the experimental devices, changes in the temperature, etc. Many agricultural experiments are subject to a two-dimensional nuisance trend, resulting from the arrangement of the trials in a two-dimensional field, see, e.g., Jacroux et al [1997] and Bailey and Williams [2007]. The objective of the experimental design in such cases is to eliminate the nuisance effects, or to provide as much information as possible on the effects of interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the experiments performed to estimate the effects of a selected set of treatments, it is common that the responses are also affected by some other experimental conditions (the covariates -e.g., time trend, block effects, the ages or the gender of the subjects in a clinical trial). The effects of the covariates are traditionally considered to be nuisance effects in the experimental design literature (e.g., Cox [1951], Majumdar and Notz [1983], Atkinson and Donev [1996], Jacroux et al [1997], Rosa and Harman [2016]). Recently, Atkinson [2015] suggested that particularly with the growing importance of personalized medicine, the covariate effects may also be of prominent interest.…”
Section: Introductionmentioning
confidence: 99%